A Charity of Mutuality and Hospitality: L'Arche's Witness to Catholic Theology - Little, Brent (Horizons, 2020)
Through the writings of Jean Vanier, this paper encourages Catholic theologians to examine critically their theological sources and their own rhetoric for the context of developmental disabilities. Specifically, this thought experiment is an invitation for the Catholic academy to consider how its theologies of charity can assist the church to reflect on its pastoral ministry to people with developmental disabilities. Some Catholic discourse is built on an assumed one-directional concept of charity that emphasizes the agency and gifts of the giver over the receiver. Such a one-sided model of hospitality tends to emphasize the giver as the person without developmental disabilities, whereas the person with disabilities is described as the receiver of hospitality; their own gifts and agency thereby are either unacknowledged or downplayed. This paper argues, instead, that Catholic theologies of charity, particularly regarding developmental disabilities, should be built on a mutuality that affirms each person's agency to be both a giver and a receiver of charity.